"Alone means nothing." The role of the Unitarian Signifier in the genesis of the phrastique sense: How does the meaning access consciousness? (Signifiances (Signifying), 2019)
The word is a gregarious animal. To signifiy it acts in organized band and it absolutely requires the collaboration of its fellow men. For this purpose, it founds with them ephemeral associations that we use to call sentences. The sentence is an event spread over time. It only exists in the actual duration of its own deployment, and it has a mandatory « sens » [direction], an obligatory temporal orientation. The « sens » [meaning] could be nothing more than the time-oriented vector, the arrow that makes us transit (whether we are speaker or receiver) from word to word throughout the interior time of the sentence. The meaning as an arrow crossing the units of a sentence is what I intend to think about here.